We are the change : words of inspiration from civil rights leaders - Alko, Selino (Chronicle Books, 2019)
Presents a collection of quotes from individuals who fought for civil rights ranging from Frederick Douglas and Maya Angelou to Helen Keller and Barack Obama. Each quote is illustrated by a different artist and includes a personal reflection from them regarding the quote.